MONEY POLITICS: SOLUTIONS IN THE QURAN FROM A CONTEMPORARY INTERPRETATION PERSPECTIVE - Syukri Daud; Ahmad Dusuki Daulay; Iqbal Maulana; Nizar Zulmi Hasibuan; Muhammad Ayyub Roy Tama; Jasril Jasril (STAI Sebelas April Sumedang, 2025)
The phenomenon of money politics is a form of deviation in the democratic process that contradicts the principles of justice and leadership integrity. This practice is widespread during elections, where votes are traded for personal or group gain. This study aims to analyze the money politics phenomenon from the perspective of the Qur’an, using a contextual interpretation of Surah Al-Baqarah verse 188. This qualitative research uses a library-based approach with thematic and contextual exegesis. The verse prohibits consuming others' wealth unjustly, including bribing authorities to gain something unlawfully, both legally and morally. The findings reveal that money politics is a form of injustice condemned by the Qur’an, as it damages the structure of social justice and violates the trust in leadership. Contextual interpretation offers a relevant understanding of the verse in relation to today’s socio-political dynamics.